1981
DOI: 10.1017/s0021859600036868
|View full text |Cite
|
Sign up to set email alerts
|

The growth and development of cowpeas (Vigna unguiculata) under tropical field conditions

Abstract: The CO 2 exchange of leaves, pods and peduncles was measured in cowpea crops grown at Ibadan, Nigeria, using a portable infra-red gas analysis system. Most leaves had maximum rates of photosynthesis (P m ) of about 1-4 mg CO 2 /m 2 /sec and maintained this value for 20 days from full expansion. Early leaves had slightly slower rates. P m decreased when leaf temperature exceeded 35 °C. The maximum efficiency of photosynthesis, e m , was about 2 g CO 2 /E (0-045 mol CO 2 /E). e m decreased with temperature for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…The maximum rates of photosynthesis observed here of c. 20 umol/m 2 /s are lower than those reported for cv. TVX4552 by Littleton et al (1981) and lie at the bottom of the range 21-38 umol/m 2 /s for maximum rates of photosynthesis reported in 31 cowpea genotypes by Lush & Rawson (1979). No significant differences were observed between the cultivars, due probably to the generally favourable soil moisture status in 1986.…”
Section: Discussionmentioning
confidence: 80%
“…The maximum rates of photosynthesis observed here of c. 20 umol/m 2 /s are lower than those reported for cv. TVX4552 by Littleton et al (1981) and lie at the bottom of the range 21-38 umol/m 2 /s for maximum rates of photosynthesis reported in 31 cowpea genotypes by Lush & Rawson (1979). No significant differences were observed between the cultivars, due probably to the generally favourable soil moisture status in 1986.…”
Section: Discussionmentioning
confidence: 80%
“…1993, Pengelly et al. 1999), 0.8–1.05 g MJ −1 for cowpea (Littleton et al. 1979, Muchow 1985, Muchow et al.…”
Section: Resultsmentioning
confidence: 99%
“…For other cool-season grain legumes, RUE values of 0.92-1.29 g MJ )1 for fababean (Thomson andSiddique 1997, Turpin et al 2002), 0.74-1.5 g MJ )1 for lentil (McKenzie and Hill 1991, Thomson and Siddique 1997) and 0.91-1.46 g MJ )1 for field pea (Heath andHebblethwaite 1985, Thomson andSiddique 1997) have been reported. For warm-season grain legumes, these values have been reported as 0.88-1.20 g MJ )1 for soya bean (Nakaseko and Gotoh 1983, Muchow et al 1993, Pengelly et al 1999), 0.8-1.05 g MJ )1 for cowpea (Littleton et al 1979, Muchow 1985, Muchow et al 1993) and 0.8-0.94 g MJ )1 for mungbean (Muchow 1985, Muchow et al 1993. Thus, RUE of chickpea falls in the range of other grain legumes.…”
Section: Radiation Use Efficiencymentioning
confidence: 95%
“…This synchronization may be due to the correlation between development of leaf area and leaf dry weight. Studies of leaf area expansion have shown that under nonstress conditions each leaf has a well defined growth rate, which is a function of temperature (HoFSTRA et al 1977, DENNETT et al 1980, LITTLETON et al 1979. The area of single leaves is maximum at mid-position of the plant therefore the expansion of these leaves coincided with maximum rates of dry matter accumulation mid-July.…”
Section: Discussionmentioning
confidence: 99%